The secreted protein P75 of Lactobacillus rhamnosus GG regulates the SERT expression via EGFR and NF‐κB pathway. Issue 9 (16th August 2022) - Wang, Xin; Li, Ying; Hou, Junjie; Wang, Zelan; Chen, Yiming; Su, Shuai; Xu, Xin; Zhang, Jie; Zhong, Weilong; Wang, Bangmao; Wang, Yuming
Abstract: Aim: To investigate the mechanism of Lactobacillus rhamnosus GG (LGG)‐secreted protein, P75, on the regulation of the expression of serotonin transporter (SERT) through the epidermal growth factor receptor (EGFR) and nuclear factor‐κB (NF‐κB) pathway. Methods: Caco‐2 cells were stimulated with LGG supernatant (LGG‐super), protein P75, AG1478, and TNF‐α. A rat model of post‐infectious irritable bowel syndrome (PI‐IBS) was constructed and treated with phosphate‐buffered saline and LGG‐super for 4 weeks. The levels of SERT, p‐EGFR, EGFR, p‐NF‐κB, NF‐κB, p‐IκB‐α, and IκB‐α were detected by quantitative real‐time polymerase chain reaction, Western blot, immunofluorescence, and immunochemistry. Luciferase assay was used to verify the link between NF‐κB and SERT promoter. Results: LGG‐super and P75 upregulated the expression levels of SERT and p‐EGFR and decreased the expression levels of p‐IκB‐α and p‐NF‐κB. Dual luciferase assay result suggested that NF‐κB inhibited the activity of SERT promoter. In the animal experiments, 5‐HT concentration increased in the PI‐IBS Model group but decreased in the Model +LGG‐super group compared with the control. On the contrary, the expression of SERT protein was downregulated in the PI‐IBS Model group and improved in the Model +LGG‐super group. The expression of p‐EGFR was reduced and p‐NF‐κB was enhanced in the PI‐IBS Model group, whereas the expression of p‐EGFR and p‐NF‐κB was the opposite in the Model +LGG‐super group. Conclusion: LGG supernatant and its secreted protein, P75, upregulate the expression of SERT by activating EGFR and inhibiting the NF‐κB pathway. Abstract : LGG supernatant and its secreted protein, P75, upregulate the expression of SERT by activating EGFR and inhibiting the NF‐κB pathway.